2023
DOI: 10.1002/ejhf.2858
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary insights into the epidemiology, impact and treatment of secondary tricuspid regurgitation across the heart failure spectrum

Abstract: Tricuspid regurgitation secondary to heart failure (HF) is common with considerable impact on survival and hospitalization rates. Currently, insights into epidemiology, impact, and treatment of secondary tricuspid regurgitation (sTR) across the entire HF spectrum are lacking, yet are necessary for healthcare decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…concentration of natriuretic peptides, NYHA class, LVEF categories, previous hospitalizations, RV dysfunction and heart failure stage). 3,6,7,25 In this context, we demonstrated that severe tricuspid regurgitation was independently associated with higher all-cause and cardiovascular mortality in a large, contemporary, real-world population of patients with heart failure and at least one 'I NEED HELP' marker of advanced heart failure. In detail, patients with severe tricuspid regurgitation had estimated rates of 1-year all-cause and cardiovascular death of 37.1 and 29.9%, respectively, and the prognostic impact of severe tricuspid regurgitation on mortality was confirmed after extensive adjustment for a previously described model, including several covariates of interest, including those related to heart failure severity, 17,19,20 and for a subsequent model including clinically relevant variables in the context of tricuspid regurgitation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…concentration of natriuretic peptides, NYHA class, LVEF categories, previous hospitalizations, RV dysfunction and heart failure stage). 3,6,7,25 In this context, we demonstrated that severe tricuspid regurgitation was independently associated with higher all-cause and cardiovascular mortality in a large, contemporary, real-world population of patients with heart failure and at least one 'I NEED HELP' marker of advanced heart failure. In detail, patients with severe tricuspid regurgitation had estimated rates of 1-year all-cause and cardiovascular death of 37.1 and 29.9%, respectively, and the prognostic impact of severe tricuspid regurgitation on mortality was confirmed after extensive adjustment for a previously described model, including several covariates of interest, including those related to heart failure severity, 17,19,20 and for a subsequent model including clinically relevant variables in the context of tricuspid regurgitation.…”
Section: Discussionmentioning
confidence: 88%
“…13 Finally, heart failure with preserved ejection fraction, being often associated with atrial fibrillation and/or postcapillary pulmonary hypertension, is emerging as a frequent phenotype in tricuspid regurgitation patients. 25,26 Although the negative prognostic impact of tricuspid regurgitation in heart failure has been already demonstrated, 2,3,[5][6][7] Cumulative incidence of 1-year all-cause death according to tricuspid regurgitation severity. Kaplan-Meier curves for 1-year all-cause death in patients with severe tricuspid regurgitation vs. moderate tricuspid regurgitation vs. no/mild tricuspid regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate and severe TR were associated with excess mortality independent of HF subtype. 34 These findings may have important clinical implications because of a growing interest in new percutaneous devices for TR treatment. 35…”
Section: Valvular Heart Diseasementioning
confidence: 96%
“…Right‐sided HF and tricuspid regurgitation (TR) are common and strongly associated with poor quality of life and prognosis 26–28 . Russo et al 29 .…”
Section: Percutaneous Treatment Of Tricuspid Regurgitationmentioning
confidence: 99%